2021
DOI: 10.14207/ejsd.2021.v10n3p273
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Audit in the Sustainable Development of Green Economy

Abstract: The aim of the article is to present the results of a study of the main problems and prospects for sustainable development of a green economy in Ukraine, as well as, using the example of forestry, the key aspects of environmental audit in ensuring sustainable forest management are identified. The results show that environmental audit can make a positive contribution to the sustainable development of a green economy. However, in Ukraine, as in other developing countries where economic goals dominate over enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These studies have highlighted the importance of robust internal control systems and proper documentation to ensure tax compliance. However, our results add novelty to the existing body of knowledge by taking a broader perspective on the topic and supplementing the previous ones, including our research [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 84%
“…These studies have highlighted the importance of robust internal control systems and proper documentation to ensure tax compliance. However, our results add novelty to the existing body of knowledge by taking a broader perspective on the topic and supplementing the previous ones, including our research [20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 84%
“…This reform has changed the internal governance structure by strengthening the direct leadership of higher-level audit institutions over lower-level audit institutions, thus facilitating the strategic allocation of audit resources and the consolidation of audit capacity. Second, the management of audits and the provision of information impact the green economy development [46]. Vertical management auditing reform has alleviated information asymmetry and implementation bias.…”
Section: Vertical Management Auditing Reform and Carbon Productivitymentioning
confidence: 99%
“…As maintained by Nazarova et al ( 2021), the study conducted by the authors showed that environmental audits could make a positive contribution to the sustainable development of a green economy. It further states that today, only one world-famous tool provides independent analysis and recommendations for various process optimizations -audit (Nazarova et al, 2021).…”
Section: Role Of Sais and Environmental Audit In Ensuring Accountabilitymentioning
confidence: 99%